Pengembangan Aktualisasi Diri: Kajian Pustaka tentang Faktor Penghambat dan Strategi Pendukung - Fahmida Azzahra; Nur Amin Barokah Asfari (Flourishing Journal, 2024)
According to Maslow, every person has five basic needs, one of which is the need for self-actualization, which occupies the highest position in the level of needs. This article aims to determine the importance of self-actualization and the factors that influence self-actualization through a literature review method. The literature was selected based on research articles published in journals over the last five years, which were then analyzed based on aspects of the five levels of human needs according to Abraham Maslow. The analysis results show that the driving factors for self-actualization are motivation, failure, belief or mindset, courage, social relationships, and self-acceptance. There are two inhibiting factors, namely internal factors, which include not knowing one's potential, feelings of doubt and fear, and looking too simply at life, while external factors include community culture, environmental factors, and bullying. Self-actualization can be achieved through strategies such as knowing yourself, building self-confidence and self-compassion, building a growth mindset, maintaining mental health (psychological well-being), being oriented toward others (client-centered), as well as carrying out various positive activities. AbstrakMenurut Maslow, setiap orang memiliki lima kebutuhan dasar, Salah satunya kebutuhan aktualisasi diri, yang menduduki posisi tertinggi dalam tingkatan kebutuhan. Artikel ini bertujuan untuk mengetahui pentingnya aktualisasi diri beserta faktor-faktor yang memengaruhi aktualisasi diri melalui metode literature review. Pustaka dipilih berdasarkan artikel penelitian yang diterbitkan pada jurnal selama lima tahun terakhir, yang kemudian dianalisis berdasarkan aspek lima tingkat kebutuhan manusia menurut Abraham Maslow. Hasil analisis menunjukkan bahwa faktor pendorong aktualisasi diri adalah motivasi, kegagalan, keyakinan atau mindset, keberanian, hubungan sosial, dan penerimaan diri. Faktor penghambatnya terdapat dua yaitu faktor internal, yang meliputi ketidak-tahuan akan potensi yang dimilikinya, perasaan ragu dan takut, serta terlalu memandang sederhana kehidupan, sedangkan faktor eksternal meliputi budaya masyarakat, faktor lingkungan, dan bullying. Aktualisasi diri dapat dicapai melalui strategi seperti mengenali diri sendiri, membangun kepercayaan diri, mencintai diri (self-compassion), membangun pola pikir yang berkembang (growth mindset), menjaga kesehatan mental (psychological well-being), berorientasi pada orang lain (client centered), serta melakukan berbagai kegiatan positif.